The capitular text of the Responsiones of pope Gregory I to St. Augustine - Deanesly, Margaret (The journal of ecclesiastical history, 1961)
In the course of an article on these Responsiones in this Journal (x. (1559) 1–49), it was suggested that a text of these replies, long known to canonists as the ‘capitular’ text, was older than that in the Historia Ecclesiastica of Bede; and, also, that the fifth Responsio in the Bedan text, which contains the long controverted permission to marry within the third and fourth generation, was an interpolation made, possibly, if not probably, by the priest Nothelm. Nothelm had corresponded with Bede over many years, and he later became archbishop of Canterbury. The writers of the article did not know at the time that Dom Paul Meyvaert had in preparation an edition of the Responsiones based on the text as found in canonical collections. The publication of this edition is much to be desired; but, meanwhile, it seems permissible to point out that the ‘capitular’ text is found in the oldest MSS. and that the Bedan text is never found in any MS. earlier than Bede's Ecclesiastical History, written in 731. If it had been, the question of priority could not, of course, have arisen.